Understanding the Strengths of Long Term Marriages among the Malaysian Chinese: Discussion on Preliminary Proposed Ethodology - Teoh Gaik Kin; Haslee Sharil Abdullah; Lau Poh Li (Institut Sosial Malaysia, 2024)
Non-Indexed Publication